Effects of early postnatal life nutritional interventions on immune-microbiome interactions in the gastrointestinal tract and implications for brain development and function - Mullaney, Jane A.; Roy, Nicole C.; Halliday, Christine; Young, Wayne; Altermann, Eric; Kruger, Marlena C.; Dilger, Ryan N.; McNabb, Warren C. (Frontiers in Microbiology, 2022)
The gastrointestinal (GI) microbiota has co-evolved with the host in an intricate relationship for mutual benefit, however, inappropriate development of this relationship can have detrimental effects. The developing GI microbiota plays a vital role during the first 1,000 days of postnatal life, during which occurs parallel development and maturation of the GI tract, immune system, and brain. Several factors such as mode of delivery, gestational age at birth, exposure to antibiotics, host genetics, and nutrition affect the establishment and resultant composition of the GI microbiota, and therefore play a role in shaping host development. Nutrition during the first 1,000 days is considered to have the most potential in shaping microbiota structure and function, influencing its interactions with the immune system in the GI tract and consequent impact on brain development. The importance of the microbiota-GI-brain (MGB) axis is also increasingly recognized for its importance in these developmental changes. This narrative review focuses on the importance of the GI microbiota and the impact of nutrition on MGB axis during the immune system and brain developmental period in early postnatal life of infants.